Semantic chang in the book Jawahir al-Kalam in the book Jawahir al-Kalam in explaining the laws of Islam by Sheikh Muhammad Hassan al-Najafi (d. 1266 AH, 1849 AD) - Ahmed Taimour Flayyih; Dr. Mohammad Razi Mostafavinia; Dr. Rasool Dehghanzad (Journal of College of Education, 2024)
This is a research in which I tried to follow what Sheikh Muhammad Hassan al-Najafi mentioned in his book Jawahir al-Kalam in explaining the laws of Islam about an important aspect of semantic study, which is the aspect of semantic change, semantic development, or the growth of words, as some researchers expressed it, and I followed the method in it. The original analysis, as I tried to investigate what the author of Al-Jawahir mentioned about the different forms of semantic change and compare that with what was mentioned by later semantic scholars